A case of giant complicated intraductal papilloma of breast on MRI and literature review. Issue 4 (24th September 2018) - Wang, Siqi; Lou, Jianjuan
Abstract: Background: With the increasing use of image‐guided biopsy, more breast intraductal papillomas are found than ever. Most intraductal papillomas are small, ranging from several milimeters to 2 cm. Case: We described a case of giant intraductal papilloma of breast in a 19‐year‐old girl with nipple bloody discharge and rapid growth. Magnetic resonance imaging diagnostic evaluation and pathologic correlation along with review of relevant literatures are documented. The lesion was characterized by presence of mixture of cystic and solid component with cystic component occupying a large space. The solid component showed morphologic, kinetic, and diffusion weighted imaging features suggestive of malignancy. Infarction with no enhancement was noted. Cystic compartments contained hemorrhage with fluid‐fluid level formation. The patient undertook lumpectomy. Conclusion: For a giant breast tumor with mixed solid and cystic component, intraductal papilloma should be considered in the differential diagnosis.